Effects of Intermittent Kangaroo Mother Care in Preterm Low Birth Weight Babies: A Randomized Controlled Trial (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Prematurity is the largest cause of neonatal mortality. They need incubators or radiant warmers which are expensive and very difficult to arrange in a resource constraint country. Kangaroo mother care (KMC) had been proposed as an alternative to conventional neonatal care for low birthweight (LBW) babies.Objectives: To observe the benefits of Kangaroo mother care in preterm low birth weight babies.Methods: This randomized controlled trial was conducted over 6 months in Dhaka Shishu Hospital. Neonates who were